Evaluation of Major Fatty Acids Determination in Palm Oil by Gas Chromatography-Flame Ionization Detection - Moh Taufik; Hanifah Nuryani Lioe; Nancy Dewi Yuliana (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2016)
The fatty acid composition of palm oil is the major factor influencing its physical and chemical properties. The purpose of this research was to evaluate the analytical performance of major fatty acids (palmitic acid, stearic acid, oleic acid, and linoleic acid) analysis in palm oil. Triglycerides of palm oil were derivatized to fatty acid methyl esters (FAMEs) by using boron trifluoride (BF3) in methanol. FAMEs were determined by gas chromatography-flame ionization detection (GC-FID) using DB-23 capillary column as stationary phase. The studied parameters were instrument performance analysis, the efficiency of fatty acid derivatization, stability of derivatized analytes, accuracy, repeatability, intra-lab reproducibility, ruggedness, and method uncertainty. The evaluation results showed the instrument linearity at a working range of 5 to 40 mg/mL marked by coefficient of determination (R2) between 0.991-0.995. Instrument limits of detection (LOD) and instrument limits of quantification (LOQ) for 4 major fatty acids analysis were 26-35 µg/mLand 86-128 µg/mL, respectively. The increase of fatty acid concentration led to the decrease of derivatization efficiency in the fatty acids analysis. The result also showed that derivatized analytes were stable during 24 h storage at freeze temperature. The average recovery values by spiking method with the spiking concentration at 50 and 90 mg/g sample were at 75-94 % for stearic and linoleic acids analysis, however those for palmitic and oleic acids analysis were considered very low (<40 %), due to their low derivatization efficiency. Repeatability and intra-lab reproducibility of 4 major fatty acids analysis were at acceptable ranges, 0.45-1.38 % and 1.15-2.03 %, respectively. Determination by varying the volume of derivatizing agent showed the rugged method. Uncertainty of repeatability (Ur) and uncertainty of reproducibility (Ur) were ranged at 1.84-9.02 mg/g and 1.40-10.65 mg/g, respectively. This method was considerably reliable for the analysis of less abundance fatty acids in palm oil, stearic and linoleic acids.